Long-read sequencing reveals chromothripsis in a molecularly unsolved case of Cornelia de Lange syndrome - Bestetti, Ilaria; Crippa, Milena; Sironi, Alessandra; Bellini, Matteo; Tumiatti, Francesca; Ballabio, Sara; Ceriotti, Ferruccio; Memo, Luigi; Iascone, Maria; Larizza, Lidia; Finelli, Palma (Frontiers in Genetics, 2024)
Thanks to a long-read sequencing (LRS) approach, in this study, we have reported a molecularly solved case of a proband with a clinical diagnosis of Cornelia de Lange syndrome (CDLS), which is a multisystemic disorder whose causative molecular defects involve cohesin complex genes, with NIPBL located at 5p13.2 accounting for approximately 50%–60% of CDLS cases. The first-tier tests revealed an abnormal karyotype 46,XY,t(5;15)(p13;q25)dn and a preserved NIPBL sequencing. Copy number variants (CNVs) at the translocation breakpoints, in disease genes, or in probably pathogenic loci were excluded by a-CGH analysis. Through fluorescence in situ hybridization (FISH) analysis on derivative chromosome 5, the breakpoint was relocated 3 Mb far from NIPBL 5′UTR, which seemed fully maintained as FISH-probe mapping to the gene showed no split signals. Moreover, tri-color FISH revealed an apparently balanced paracentric inversion including NIPBL on derivative 5. Based on the strong clinical suspicion, we evaluated the NIPBL transcript by RT-qPCR that revealed a normal amount of transcript till exon 22 and a halved amount of the transcript from exon 23 to 3′UTR, indicating the expression of a truncated transcript probably leading to a defective protein. Despite RT-qPCR confirmed the patient’s CDLS clinical diagnosis, the molecular mechanism underlying this event remained to be an unsolved challenge for years. The LRS approach with nanopore technologies was able to fill the gap in this complex scenario and highlighted a chromothripsis event marked out at 5p13.2 by 36 breaks clustered in a 7.3-Mb region. The NIPBL gene was disrupted by 16 breaks and the resulting fragments were relocated in different positions and orientations. LRS confirmed the previous findings, and it has been proven to be crucial to define the complex chromosomal rearrangement in this patient which escaped current diagnostic investigations. Its application in the clinical practice will contribute to solve the unsolved.